Knowledge-sharing and social interaction within MNEs - Noorderhaven, Niels; Harzing, Anne-Wil (Journal of International Business Studies, 2009)
Social interaction between managers from different units of a multinational enterprise (MNE) has been shown to be an important factor stimulating intra-MNE knowledge-sharing. Face-to-face social interactions form a communication channel particularly conducive to the transfer of tacit, non-codified knowledge. But intensive social interaction also provides opportunities for social construction of knowledge in a learning dialogue. The first explanation (sender–receiver) makes us expect social interaction to moderate positively the effects of the factors giving rise to knowledge flows in the first place, such as differences in capabilities between MNE subsidiaries. The second perspective (social learning) also grants an independent effect to social interaction as a main factor stimulating intra-MNE knowledge flows. We formulate hypotheses based on both perspectives, and test these on data from 169 MNE subsidiaries. Our findings show a considerable main effect of social interaction on all intra-MNE knowledge flows, confirming the expectations based on the social learning model. Interaction effects, based on the predictions of the sender–receiver model, are only partly confirmed. These findings suggest that future research should devote more attention to the social constitution of MNE knowledge.